2017
DOI: 10.1002/2016jc012587
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Mesoscale Dynamics on Ocean Deep Convection: The 2012–2013 Case Study in the Northwestern Mediterranean Sea

Abstract: Winter 2012–2013 was a particularly intense and well‐observed Dense Water Formation (DWF) event in the Northwestern Mediterranean Sea. In this study, we investigate the impact of the mesoscale dynamics on DWF. We perform two perturbed initial state simulation ensembles from summer 2012 to 2013, respectively, mesoscale‐permitting and mesoscale‐resolving, with the AGRIF refinement tool in the Mediterranean configuration NEMOMED12. The mean impact of the mesoscale on DWF occurs mainly through the high‐resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 94 publications
(204 reference statements)
1
20
0
Order By: Relevance
“…As pointed out by Leger et al (), "L'Hévéder et al () and Somot et al (), numerical simulations are very sensitive to the initial conditions with regards to winter convection and numerical outputs, including operational products like MERCATOR PSY2V4R4 (Estournel et al, ), have generally serious difficulties to describe well the intermediate and deep layers, because stratification is influenced by initial conditions derived from smoothed climatologies encompassing decades of observations. Waldman et al () and Estournel et al () showed it is possible to correct the initialization and forcing of their model and to significantly improve the realism of the simulations using the DEWEX data set both for initial conditions correction in Summer and later validation.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…As pointed out by Leger et al (), "L'Hévéder et al () and Somot et al (), numerical simulations are very sensitive to the initial conditions with regards to winter convection and numerical outputs, including operational products like MERCATOR PSY2V4R4 (Estournel et al, ), have generally serious difficulties to describe well the intermediate and deep layers, because stratification is influenced by initial conditions derived from smoothed climatologies encompassing decades of observations. Waldman et al () and Estournel et al () showed it is possible to correct the initialization and forcing of their model and to significantly improve the realism of the simulations using the DEWEX data set both for initial conditions correction in Summer and later validation.…”
Section: Discussionmentioning
confidence: 57%
“…This data set was then used for validation purposes to assess the realism of numerical simulations in particular in terms of timing and geography of the phenomena as well as in terms of quantitative estimates of the deep water formation rate (Waldman et al, ) and in terms of mesoscale and submesoscale processes (Damien et al, ; Waldman et al, ) by performing similar diagnostics in the observations and the simulations, and sensitivity studies. They were thus able to reach a better understanding of deep convection processes from autumn to winter together with quantitative estimates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the turbulent mesoscale dynamics, primarily stemming from baroclinic instability, is intrinsic to the ocean itself and can modulate deep convection through the restratification process. The question of how important this IOV is to the total variability of deep convection activity in the NWMed, which has been addressed at the daily time scale by Waldman, Somot, et al () and Waldman, Herrmann, et al (), remains open at the interannual and climatic time scales, which are the focus of the present work.…”
Section: Introductionmentioning
confidence: 90%